PERCEPTION OF CHARACTER EDUCATION THROUGH WISDOM OF LOCAL HISTORY OF BANTEN FOR STUDENTS OF OPEN UNIVERSITY IN BANTEN PROVINCE - Wawan Suharmawan; Iis Solihat (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2018)
Abstract. This article aims to examine the perceptions of UPBJJ-UT students in Serang City about character education through local wisdom in Banten province. The data were collected through Focused-Group Discussion (FGD), questionnaire distribution, and observation. The data were analysed qualitatively. The data then were validated by using content validation. Meanwhile, the qualitative data were validated through triangulation. Student Perceptions UPBJJ-UT Serang City about character education through local history wisdom in Banten Province is seen as something that should be developed and implanted to the students. local history of Banten wisdom gained through the surrounding environment that adopts the local culture of indigenous people in Banten Province (Lebak District with local culture Baduy Tribe, and Regency of Serang with Domas Kingdom and Kingdom of Banten Lama)Keyword: wisdom local, and character education